Analysis of labour conditions in the Spanish social economy entities from a gender perspective - Santero Sanchez, Rosa; Castro Núñez, Belén (REVESCO. Revista de Estudios Cooperativos, 2016)
The values shared by social economy enterprises generate a differentiated behaviour of these entities in relation to their staff composition, the work conditions, their productive specialisation and their geographical location compared to the profit seeking firms (corporations and limited liability companies). This differentiated behaviour constitutes an important contribution to social cohesion, and in particular from a gender perspective, it foster a higher participation in labour market and better labour conditions. The mail goal of the paper is to evaluate the existence of the differentiated behavior of social economy entities in terms of equal opportunities and labour conditions, focusing in Spain. We use the Continuous Work History Sample (MCVL) for the year 2010 and identify the target group and the control group that are statistically comparable in terms of size and industry. We first analyze the differences between workers conditions in both groups applying parametric and nonparametric test for average differences. Secondly, we focus on wages discrimination, using Oaxaca-Blinder decomposition technique. Results show that social economy entities provide better conditions in access to employment and labour stability, and also show lower gender wage discrimination.